2008
DOI: 10.1186/1475-2875-7-87
|View full text |Cite
|
Sign up to set email alerts
|

Escalating Plasmodium falciparum antifolate drug resistance mutations in Macha, rural Zambia

Abstract: Background: In Zambia the first-line treatment for uncomplicated malaria is artemisinin combination therapy (ACT), with artemether-lumefantrine currently being used. However, the antifolate regimen, sulphadoxine-pyrimethamine (SP), remains the treatment of choice in children weighing less than 5 kg and also in expectant mothers. SP is also the choice drug for intermittent preventive therapy in pregnancy and serves as stand-by treatment during ACT stock outs. The current study assessed the status of Plasmodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
1
7
1
Order By: Relevance
“…The results showed a complex mixture of pfdhfr/pfdhps haplotypes in Luanda as already reported in other six provinces of Angola [ 25 , 26 ]. The 164L mutation was not disclosed, corroborating the findings of other nearby African countries [ 27 - 29 ]. The pfdhfr 50R SNP herein found confers an increased level of resistance to pyrimethamine and this mutation is characteristic from South-American isolates [ 30 ] and, it was found only once in Africa, when Kenyan isolates were evaluated [ 31 ].…”
Section: Discussionsupporting
confidence: 85%
“…The results showed a complex mixture of pfdhfr/pfdhps haplotypes in Luanda as already reported in other six provinces of Angola [ 25 , 26 ]. The 164L mutation was not disclosed, corroborating the findings of other nearby African countries [ 27 - 29 ]. The pfdhfr 50R SNP herein found confers an increased level of resistance to pyrimethamine and this mutation is characteristic from South-American isolates [ 30 ] and, it was found only once in Africa, when Kenyan isolates were evaluated [ 31 ].…”
Section: Discussionsupporting
confidence: 85%
“…SP has been in use for over two decades in Zambia and due to drug pressure parasite resistance is expected to be high as is evident from trends analysis in populations were SP has been used for even shorter periods of time. Data from southern Zambia showed that by 2006, the prevalence of dhfr and dhps mutants had escalated rapidly since 1988, and that the quintuple ( dhfr triple + dhps double) mutant associated with highest levels of SP clinical failure was starting to be seen (6.5%) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to type 1 antifolates (pyrimethamine, chlorproguanil, trimethoprim) has been associated with amino acid substitutions in the Pfdhfr gene while resistance to type II antifolates (sulfonamides: sulfadoxine and dapsone) are associated with mutations in P . falciparum dihydropteroate synthase ( Pfdhps ) gene [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%